Child deaths due to injury in the four UK countries: a time trends study from 1980 to 2010. - Pia Hardelid; Jonathan Davey; Nirupa Dattani; Ruth Gilbert; Working Group of the Research and Policy Directorate of the Royal College of Paediatrics and Child Health (PLoS ONE)
Background Injuries are an increasingly important cause of death in children worldwide, yet injury mortality is highly preventable. Determining patterns and trends in child injury mortality can identify groups at particularly high risk. We compare trends in child deaths due to injury in four UK countries, between 1980 and 2010. Methods We obtained information from death certificates on all deaths occurring between 1980 and 2010 in children aged 28 days to 18 years and resident in England, Scotland, Wales or Northern Ireland. Injury deaths were defined by an external cause code recorded as the underlying cause of death. Injury mortality rates were analysed by type of injury, country of residence, age group, sex and time period. Results Child mortality due to injury has declined in all countries of the UK. England consistently experienced the lowest mortality rate throughout the study period. For children aged 10 to 18 years, differences between countries in mortality rates increased during the study period. Inter-country differences were largest for boys aged 10 to 18 years with mortality rate ratios of 1.38 (95% confidence interval 1.16, 1.64) for Wales, 1.68 (1.48, 1.91) for Scotland and 1.81 (1.50, 2.18) for Northern Ireland compared with England (the baseline) in 2006-10. The decline in mortality due to injury was accounted for by a decline in unintentional injuries. For older children, no declines were observed for deaths caused by self-harm, by assault or from undetermined intent in any UK country. Conclusion Whilst child deaths from injury have declined in all four UK countries, substantial differences in mortality rates remain between countries, particularly for older boys. This group stands to gain most from policy interventions to reduce deaths from injury in children.